The Influence of Artificial Intelligence on Brand Preference of Syariah Banking Customers in Bandung Raya - Safitri, Feni Malinda; Suhartanto, Dwi; Setiawan, Setiawan (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The rapid advancement of Artificial Intelligence (AI) technology has brought significant transformations across various industries and reshaped how consumers interact. This study highlights the role of AI-based chatbots and analytics in shaping marketing strategies and customer service. Chatbots enable round-the-clock service, support multiple languages, and reduce operational costs. Meanwhile, AI-driven marketing facilitates a more personalized approach by leveraging data to predict consumer needs, accelerate decision-making, and influence purchasing behavior, despite the inherent risk of bias. Grounded in the Stimulus-Organism-Response (S-O-R) model, this research focuses on the influence of AI on brand preference in the context of Islamic banking in Indonesia. The study aims to support Islamic banks in designing AI-driven marketing activities and formulating more effective branding and marketing strategies. A survey was conducted with over 400 respondents. The findings reveal that consumers appreciate the speed and personalization offered by AI-powered services; however, they remain aware of AI’s limitations in emotional understanding. This indicates that while AI enhances engagement, further development is needed to create more emotionally intuitive AI-driven experiences.